Electrochemical Fabrication of Prussian Blue Nanocube‐decorated Electroreduced Graphene Oxide for Amperometric Sensing of NADH. Issue 5 (7th February 2019) - Eryiğit, Mesut; Temur, Elif; Özer, Tuba Öznülüer; Doğan, Hülya Öztürk
Abstract: In this study, Prussian blue (PB) film on the electroreduced graphene oxide (ERGO)‐modified Au electrode surface (ERGO/PB) is easily prepared by means of cyclic voltammetric technique in the mixture of K3 Fe(CN)6 and FeCl3 . Its electrochemical behaviors for NADH biosensor are studied. The structural and morphological characters of modified electrode material are analyzed with using of XPS, XRD, Raman, EDS, and SEM techniques. ERGO/PB hybrid nanocomposite for NADH biosensor is exhibited to the higher catalytic effect (linear range from 1.0 to 100 μM, detection limit of 0.23 μM at S/N=3) compared to naked Au, ERGO‐modified Au, and PB‐modified Au electrodes. In addition to, ERGO/PB electrode was used to voltammetric and amperometric detection of H2 O2 . ERGO/PB electrodes also showed the same behavior as the NADH sensor. This ERGO/PB‐modified electrode supplied a simple, new, and low‐cost route for amperometric sensing of both NADH and H2 O2 . Abstract :